Experimental investigation on heat transfer and pressure drop of ZnO/ethylene glycol-water nanofluids in transition flow. (25th January 2016) - Li, Yanjun; Fernández-Seara, José; Du, Kai; Pardiñas, Ángel Álvarez; Latas, Luis Lugo; Jiang, Weixue
Highlights: Heat transfer enhancement of ZnO–ethylene glycol nanofluids was studied. Nanofluids' physical properties were studied at different temperatures up to 70 °C. 2.5 wt.% ZnO nanofluids enhanced the heat transfer coefficient up to 30%. Heat transfer may be deteriorated due to deposition at higher particle fractions. Nanoparticles in different flow regimes have different effects on the pressure drop. Abstract: Transition regime convection heat transfer coefficients of zinc oxide/ethylene glycol–water (ZnO/EG-W) nanofluid in a circular pipe were investigated experimentally where the mass fraction of nanoparticles in the base fluid is from 0 to 5 wt.% and at operating temperatures. Different ZnO/EG-W mass concentration nanofluids were prepared, and the physical and thermal transport properties including density, thermal conductivity, specific heat capacity and viscosity were measured and the results were compared with the base fluid. It was found that the nanofluid has maximum of 30% higher heat transfer coefficient compared to base fluid at mass fraction of 2.5 wt.%, whereas at higher values of the nanoparticles' mass concentration of 5 wt.%, the heat transfer coefficient decreases. There is an optimal value of the concentration for the nanoparticles to have the maximal enhancement of the heat transfer. The measurements also showed that the pressure drop of nanofluid was higher than that of the base fluid in a turbulent flow regime. However, there was no significant increase in pressure drop at laminar flow. Our results demonstrated that the ZnO/EG-W nanofluid might be a promising alternative for conventional coolants.